Neurologic injuries after primary total ankle arthroplasty: prevalence and effect on outcomes. Issue 1 (December 2015) - Primadi, Andri; Xu, He-Xing; Yoon, Taek-Rim; Ryu, Je-Hwang; Lee, Keun-Bae
Abstract Background Neurologic injuries are complications that can arise after total joint arthroplasty. However, no comprehensive study has been conducted on peripheral nerve injuries after total ankle arthroplasty. The purpose of the present study was to identify the prevalence of neurologic injury following primary total ankle arthroplasty, the predisposing factors, and evaluate the effect on clinical outcomes. Methods We retrospectively analyzed 150 consecutive primary total ankle arthroplasty using the mobile-bearing prosthesis between January 2005 and December 2011, in 150 patients with symptomatic ankle end-stage arthritis. All the patients were divided into groups according to whether they had postoperative peripheral neuropathy (23 patients) or not (127 patients). We investigated the prevalence, predisposing factors, and effect on clinical outcomes of neurologic injuries. The mean age was 61.3 years, and the mean follow-up period was 41.8 months. Results There were 23 nerve injuries (15.3 %), including nine in posterior tibial nerves, six superficial peroneal nerves, six deep peroneal nerves, one saphenous nerve, and one sural nerve. Neurologic injury was significantly associated with the development of posttraumatic osteoarthritis, but it was not significantly associated with other predisposing factors, such as age, gender, body mass index, and symptom duration. Of the 23 nerve injuries, 13 (56.5 %) presented a complete, spontaneous recovery, 9 (39.1 %) presented an incomplete recovery, and 1 (4.3 %) presented no recovery. The patients with neurologic injury had significantly lower American Orthopaedic Foot and Ankle Society scores and lower levels of patient satisfaction. Conclusions The results of this study suggest that the prevalence of neurologic injury after total ankle arthroplasty is considerable, and that neurologic injury is associated with low levels of patient satisfaction and poor clinical outcomes at mean of 3 years, postoperatively. Care is needed to reduce the occurrence of neurologic injuries.